Magnetism of uranium/iron multilayers: II. Magnetic properties - Beesley, A; Zochowski, S; Thomas, M; Herring, A; Langridge, S; Brown, S; Ward, R; Wells, MR; Springell, R; Stirling, W; Lander, G (2004)
Well-defined U/Fe multilayers of varying layer thicknesses and bilayer repeat numbers were prepared by a dc magnetron sputtering method. Polarized neutron reflectometry, off-specular neutron diffraction and magnetic moment measurements were used to determine the physical properties of the multilayers leading to an evaluation of the magnetic moments associated with the U and Fe atoms. The multilayers exhibit ferromagnetic behaviour with the easy axis in the plane of the multilayer. The saturation magnetization was found to increase with increasing Fe-layer thickness and the magnetic moment averaged over the structured iron layers was below the bulk value of 2.2 μB/Fe atom. No anomalies were observed in the magnetization from 4.2 to 375 K in temperature-dependent scans at 0.005 and 0.1 T or in magnetic field scans from 0 to 7 T at 4.2 and 295 K. The hysteresis curves exhibited a small degree of perpendicular magnetic anisotropy. The Curie temperatures for the multilayers were.determined from ac susceptibility measurements and were found to be less than the bulk Fe value of 1043 K.